Literature Review: Use of (Moringa oleifera) Leaves Against Inflammation - Rita Hartati Rambe; Elsa Yuniarti (Jurnal Biologi Tropis, 2023)
The Moringa plant is known as a nutritious plant, has health benefits and can be used in the industrial sector. Moringa plants contain flavonoids, saponins and polyphenols which are known to have anti-inflammatory activity. The aim of this research is to conduct a literature review to gather general information about the use of Moringa leaves for inflammation. The research method applied is a literature review by searching for relevant sources on Google Scholar in the period 2010-2022. Based on a literature review of various research results, it is proven that the content of Moringa leaves has a significant effect on inflammation.